2015
DOI: 10.1186/s12939-014-0131-1
|View full text |Cite
|
Sign up to set email alerts
|

How the government intervention affects the distribution of physicians in Turkey between 1965 and 2000

Abstract: IntroductionOne of the main weaknesses of the health system in Turkey is the uneven distribution of physicians. The diversity among geographical districts was huge in the beginning of the 1960s. After the 1980s, the implementation of a two-year compulsory service for newly graduated physicians is an interesting and specific experience for all countries. The aim of this study is to analyse the distribution of physicians, GPs and specialists between the years 1965-2000 and the efficiency of the strict 15 year go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
94
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 21 publications
(31 reference statements)
11
94
0
1
Order By: Relevance
“…Similar to our findings, Katulanda et al and De Silva et al found a positive association between obesity and increasing income levels in Sri Lankan adults [20, 67]. India and Bangladesh similarly show an increase in obesity prevalence rates with increase in education levels and living standards [68, 69].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our findings, Katulanda et al and De Silva et al found a positive association between obesity and increasing income levels in Sri Lankan adults [20, 67]. India and Bangladesh similarly show an increase in obesity prevalence rates with increase in education levels and living standards [68, 69].…”
Section: Discussionsupporting
confidence: 90%
“…The concentration index has been widely used for measuring income-related inequalities in the health sector internationally, whilst its decomposition analysis has been increasingly adopted to study inequality determinants [1113]. The majority of previous studies investigated health utilization inequality in China, with very limited study focused on health status [12, 14].…”
Section: Introductionmentioning
confidence: 99%
“…This is an example of what have been elsewhere referred to as capital conversions [44] or capital acquisition interplays [28], social processes whereby one form of capital facilitates the successful acquisition of another form of capital and consequently good health. In this case, institutionalized cultural capital in the form of educational credentials is presumably used by men and women to procure high-paying jobs (or spouses with high-paying jobs) and amass financial wealth which then mitigate the development of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The plausibility of this multigenerational line of causality notwithstanding, empirical studies that relate processes of intergenerational transmission of capital to adult health are rare [27, 28]. In particular, research on the relationship between processes of intergenerational capital transmission and depression, an important domain of mental health, is nonexistent.…”
Section: Introductionmentioning
confidence: 99%